Wishtree [large type] - Applegate, Katherine (Thorndike Press, a part of Gale, a Cengage Company, 2018)
"Red is an oak tree who is many rings old. Red is the neighborhood "wishtree" -- people write their wishes on pieces of cloth and tie them to Red's branches. Along with a crow named Bongo and other animals who seek refuge in Red's hollows, this wishtree watches over the neighborhood. You might say that Red has seen it all. Until a new family moves in. Not everyone is welcoming, and Red's experience as a wishtree is more important than ever"--